2011
DOI: 10.1371/journal.pgen.1002411
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Phylogenomic View of the Seed Plants

Abstract: A novel result of the current research is the development and implementation of a unique functional phylogenomic approach that explores the genomic origins of seed plant diversification. We first use 22,833 sets of orthologs from the nuclear genomes of 101 genera across land plants to reconstruct their phylogenetic relationships. One of the more salient results is the resolution of some enigmatic relationships in seed plant phylogeny, such as the placement of Gnetales as sister to the rest of the gymnosperms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 103 publications
11
119
3
1
Order By: Relevance
“…Although most genes involved in DNA methylation are conserved across angiosperm species, these genes have not been extensively studied in gymnosperms, and the existence of Pol V in gymnosperms has been controversial (13). Previous studies showed that many subunits of RNA POLYMERASE IV (Pol IV) were conserved across land plants.…”
Section: Resultsmentioning
confidence: 99%
“…Although most genes involved in DNA methylation are conserved across angiosperm species, these genes have not been extensively studied in gymnosperms, and the existence of Pol V in gymnosperms has been controversial (13). Previous studies showed that many subunits of RNA POLYMERASE IV (Pol IV) were conserved across land plants.…”
Section: Resultsmentioning
confidence: 99%
“…Gnetales-sister (Lee et al 2011) Angiosperms Eudi + Mag (Lee et al 2011) Eudi + Mag/Chl (Burleigh et al 2009) Mono + Eudi (Soltis et al 2011) A…”
Section: Relationships Among Streptophytic Algal Lineages and Land Plmentioning
confidence: 99%
“…Increasingly, analyses of nuclear genes assembled from publicly available genome or transcriptome databases are being used to assess previously recalcitrant relationships within the green tree of life (27,29,35,(51)(52)(53).…”
mentioning
confidence: 99%
“…Reports on sRNA studies in gymnosperm seeds have been lacking so far, but previous work on conifer sRNAs have reached different and contradicting conclusions regarding the presence of 24-nt sRNAs, typically associated with hetsiRNAs, in the sRNA transcriptome of the conifers clade Morin et al 2008;Lee et al 2011;Chávez-Montes et al 2014;Wan et al 2012;Zhang et al 2012bZhang et al , 2013bNystedt et al 2013;Niu et al 2015). In somatic embryo-derived material from the conifer Japanese larch (Larix leptolepis) the presence of significant amounts of 24-nt sRNAs has been reported (Zhang et al 2012b(Zhang et al , 2013b, but it would be interesting to check for the presence of these sRNAs in conifer seeds.…”
Section: Abundance Of Small Rnas In Seed Tissuesmentioning
confidence: 99%